Anionic Surfactant Binding to Lysozyme and Hydrophobic Interactions Effect to the Binding: A Novel Binding Model - CHAMANI, J.; DEHGHAN-NAERI, N.; SALEH-MOGHADAM, M. (Asian Journal of Chemistry, 2010)
The interaction between anionic surfactants sodium dodecyl sulfate, sodium octyl sulfate and sodium decyl sulfate in various concentrations at pH 7.4 was investigated by the methods of fluorescence and circular dichroism techniques. Fluorescence data showed that the fluorescence quenching of lysozyme by anionic surfactants was the result of the formation of the surfactant-lysozyme complex. According to the Stern-Volmer equation, binding constant between anionic surfactants and lysozyme were obtained to be 21.08 × 103, 6.054 × 103 and 9.404 × 103 L mol-1, respectively, indicating that the binding of sodium dodecyl sulfate to protein is more than others. Based on the results obtained, with increasing chain length of the surfactants, DGº (H2O) has become more positive. Therefore, hydrophobic interactions were the dominant intermolecular force in stabilizing the complex. The conformational investigation showed that the presence of sodium dodecyl sulfate decreased and in presence of sodium octyl sulfate, sodium decyl sulfate increased the a-helical content of lysozyme.